Spectroscopic, Structural, and Kinetic Investigation of the Ultrafast Spin Crossover in an Unusual Cobalt(II) Semiquinonate Radical Complex. Issue 9 (16th January 2017) - Rupp, Fabian; Chevalier, Katharina; Graf, Michèle; Schmitz, Markus; Kelm, Harald; Grün, Anneken; Zimmer, Manuel; Gerhards, Markus; van Wüllen, Christoph; Krüger, Hans‐Jörg; Diller, Rolf
Abstract: A comprehensive spectroscopic and structural investigation of [Co II (l ‐ N4 t Bu2 )(dbsq)][B( p ‐C6 H4 Cl)4 ] (1, l ‐N4 t Bu2 = N, N ′‐di‐ tert ‐butyl‐2, 11‐diaza[3.3](2, 6)pyridinophane, dbsq 1− =3, 5‐di‐ tert ‐butylsemiquinonate), the first known octahedral complex with a low‐spin (ls) Co II semiquinonate ground state, is reported. Above 200 K, solids as well as solutions of1 exhibit thermally induced spin‐crossover (SCO) from the ls to the high‐spin (hs) Co II semiquinonate state instead of the frequently observed valence tautomerism from ls Co III catecholate to hs Co II semiquinonate. DFT calculations demonstrate that the (closed shell) Co III catecholate suffers from a triplet instability leading to the ls Co II semiquinonate ground state. The thorough temperature‐dependent spectroscopic study of the SCO enables a photophysical investigation. Thus, by selective photoexcitation of the ls fraction of1 in solution at room temperature, ultrafast conversion to the hs state is observed using femtosecond electronic and IR‐vibrational (infrared) transient absorption spectroscopy. The kinetics of the photocycle is described by a stretched exponential with τ =3.3–3.6 ps and β =0.52–0.54, representing an upper limit for the hs–ls relaxation time. This is, to our knowledge, the fastest interconversion ever determined for a SCO complex, and is attributed to the special situation that in1 a Co II complex is coordinated to a π‐radical ligand allowing very efficient coupling between the ls and hs spin states. Abstract : It was the spin and not the valence : In this unique low‐spin Co II semiquinonate complex, spin crossover is observed both in solid state and in solution, instead of valence tautomerism. The co ordinated radical ligand is responsible for ultrafast spin‐state equilibration, which is characterized by femtosecond transient absorption spectroscopy.